Phase transformations at interfaces: Observations from atomistic modeling. Issue 5 (October 2016) - Frolov, T.; Asta, M.; Mishin, Y.
Graphical abstract: Highlights: We review recent atomistic simulations of structural phase transitions at grain boundaries. New improved simulation methodology reveals that GB phase transitions are more common than previously thought. The simulations demonstrate the effects of transitions on GB segregation, migration and interaction with point defects. We discuss new challenges in thermodynamic treatment and modeling of grain boundary phase transitions. Abstract: We review the recent progress in theoretical understanding and atomistic computer simulations of phase transformations in materials interfaces, focusing on grain boundaries (GBs) in metallic systems. Recently developed simulation approaches enable the search and structural characterization of GB phases in single-component metals and binary alloys, calculation of thermodynamic properties of individual GB phases, and modeling of the effect of the GB phase transformations on GB kinetics. Atomistic simulations demonstrate that the GB transformations can be induced by varying the temperature, loading the GB with point defects, or varying the amount of solute segregation. The atomic-level understanding obtained from such simulations can provide input for further development of thermodynamics theories and continuous models of interface phase transformations while simultaneously serving as a testing ground for validation of theories and models. They can also help interpret and guide experimental work in this field.